Effects of Dietary Antioxidant Intake on Lung Functions in Construction Workers in Surabaya - Lorensia, Amelia; Suryadinata, Rivan Virlando; Mahfidz, Ikhwan Khairul (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Oxidative stress is a condition where the imbalance between oxidants and antioxidants in the body. Vitamins A, C, and E are antioxidants that can inhibit the activity of antioxidant compounds so that these levels become balanced. The research purpose is to know the difference in intake of antioxidants in the diet and the intake effect on lung function in mason who suffer from respiratory and who do not suffer from respiratory. The study design was observational methods Retrospective with purposive and consecutive sampling. Measured variables such as vitamin A, C, and E to Recall 24h and conditions of lung function. Namely % FEV1 and FVC% with a handheld spirometer. The study sample consisted of 79 people who suffer from respiratory and 79 without respiratory distress. The results showed no significant difference between antioxidant intake in the group of interference and without interference (p=0.05). Artifacts relationship between antioxidant intake with lung function (sig.0,05). Intake of vitamin A on lung function has a value of p = 0.05, which means associated with lung function but are very weak correlation (correlation coefficient value -0.036) while vitamin C and E have a value of p=1.000, which means there is a relationship and is a very weak correlation (correlation coefficient value of -0.036). The results showed no significant difference between antioxidant intake in the group of interference and without interference (p = 0.05). Artifacts relationship between antioxidant intake with lung function (sig. 0,05). Intake of vitamin A on lung function has a value of p=0.05, which means associated with lung function but are very weak correlation (correlation coefficient value -0.036) while vitamin C and E have a value of p = 1.00, which means there is a relationship and is a very weak correlation (correlation coefficient value of -0.036). The results showed no significant difference between antioxidant intake in the group of interference and without interference (p=0.05). Artifacts relationship between antioxidant intake with lung function (sig.0,05). Intake of vitamin A on lung function has a value of p=0.05, which means associated with lung function but are very weak correlation (correlation coefficient value -0.036) while vitamin C and E has a value of p=1.00, which means there is a relationship and is a very weak correlation (correlation coefficient value of -0.036).